2023
DOI: 10.3390/chemistry5020074
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Supramolecular Synthons in Cocrystals of Two Racetams with 4-Hydroxybenzoic Acid and 4-Hydroxybenzamide Coformers

Abstract: Structures of three cocrystals of nootropic racetams were studied. They included two cocrystals of phenylpiracetam (PPA) with 4-hydroxybenzoic acid (HBA) with different stoichiometries, PPA·HBA and PPA·2HBA, and cocrystal of 2-(4-phenyl-2-oxopyrrolidin-1-yl)-N’-isopropylideneacetohydrazide (PPAH) with 4-hydroxybenzamide (HBD), PPAH·HBD·(acetone solvate). X-ray study of the pure forms of PPA and PPAH was also carried out to identify variations of molecular synthons under the influence of conformers. The cocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Beyond the fact that cocrystals are solid forms different from the solid reactants they originate, literature also lately reported several examples of polymorphic cocrystals and solvate cocrystals. These are mostly produced by conventional methods. Though the potentiality of scCO 2 -based techniques to control polymorphism has been addressed for homocrystals, only few articles reported polymorphism of cocrystals, , one for the production of a solvate, and none has ever reported the obtention of a cocrystal solvate.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the fact that cocrystals are solid forms different from the solid reactants they originate, literature also lately reported several examples of polymorphic cocrystals and solvate cocrystals. These are mostly produced by conventional methods. Though the potentiality of scCO 2 -based techniques to control polymorphism has been addressed for homocrystals, only few articles reported polymorphism of cocrystals, , one for the production of a solvate, and none has ever reported the obtention of a cocrystal solvate.…”
Section: Introductionmentioning
confidence: 99%
“…Cocrystallization has become an essential method within the pharmaceutical industry for the modification of the physicochemical properties of active pharmaceutical ingredients (APIs), such as solubility, dissolution rate, bioavailability, and stability. The existence of cocrystals in various stoichiometries between the same API and coformer can expand the repertoire of possible solid forms for a given API. Consequently, the screening of cocrystals with diverse stoichiometries has garnered considerable attention due to its inherent advantages. For instance, extensive research on the cocrystallization of caffeine (CAF) with 4-hydroxybenzoic acid (4-HBA) has been conducted using both experimental and computational methods . Interestingly, it has been demonstrated that CAF and 4-HBA cocrystallize in a 1:1 molar ratio, resulting in a mixture of (2:1) and (1:2) cocrystals, which contradicts computational predictions that suggest greater stability for the (1:1) cocrystals. , However, the formation of CAF/4-HBA (1:1) cocrystals has not yet been achieved.…”
Section: Introductionmentioning
confidence: 99%